The Habitus Made Me Do It: Bourdieu's Key Concept as a Substruction of the Monad - Belvedere, Carlos Daniel (2013)
My claim is that Bourdieu's concept of habitus is not consistent and its ambiguities conceal an imprecision concerning the subject of social action. Indeed, Bourdieu defines habitus in three different ways: as a capacity, as a set of dispositions, and as a scheme for practice. That is why he cannot solve the problem of the duality of agent and habitus and produces a problem of fundamentation, as we can see in his troubles to determine which is the substratum of social actions. Though Bourdieu claims he borrows the concept of habitus from Husserl and other phenomenologists, many divergences can be stated in the way they conceive it. Unlike Bourdieu, phenomenology can establish precise relations of fundamentation between agent, habitus and the ego because it avoids the fallacy of the wrong level involved in the attribution of systemic properties to personal eogic structures. Accordingly, it provides a consistent, precise concept of the habitus.